The Benefits and Pitfalls of Google Scholar. Issue 4 (13th June 2018) - Jensenius, Francesca R.; Htun, Mala; Samuels, David J.; Singer, David A.; Lawrence, Adria; Chwe, Michael
ABSTRACT: Google Scholar (GS) is an important tool that faculty, administrators, and external reviewers use to evaluate the scholarly impact of candidates for jobs, tenure, and promotion. This article highlights both the benefits of GS—including the reliability and consistency of its citation counts and its platform for disseminating scholarship and facilitating networking—and its pitfalls. GS has biases because citation is a social and political process that disadvantages certain groups, including women, younger scholars, scholars in smaller research communities, and scholars opting for risky and innovative work. GS counts also reflect practices of strategic citation that exacerbate existing hierarchies and inequalities. As a result, it is imperative that political scientists incorporate other data sources, especially independent scholarly judgment, when making decisions that are crucial for careers. External reviewers have a unique obligation to offer a reasoned, rigorous, and qualitative assessment of a scholar's contributions and therefore should not use GS.